PENGANGGURAN SERTA DAMPAKNYA TERHADAP PERTUMBUHAN DAN PEMBANGUNAN EKONOMI - Devit Prasetyo Sejati (GoAcademica Research dan Publishing, 2020)
Unemployment in indonesia must be resolved immediately because it greatly affects economic growth and development. The impact of unemployment spreads to all sectors of the economy. Unemployment is also an obstacle in the process of economic development. How could we not feel the impact now. The economi is in decline, poverty is everywhere which ultimately results in a lack of social welfare and hinders economic growth. Moreover, Indonesia is a country that isstill developing. Problems like this must be resolved immediately with various policies from the government. In addition, there must also be a willingness from the public to move forward to reduce unemployment in order to create social welfare and improved economic growth.